Colonial and Cosmopolitan Visions in Ade Irma Elvira’s Merangkul Beruang Merah (Hugging The Red Bear) - Retno Wulandari; Sulistya Ningtyas; Mytha Candria (Politeknik Negeri Sriwijaya, 2026)
This study analyzes the colonial and cosmopolitan visions in the novel Merangkul Beruang Merah (Hugging the Red Bear) (2016) by Ade Irma Elvira, which tells the story of the struggle of the main character, who comes from humble, ordinary family, to obtain a scholarship to Russia and live in that country. Using postcolonial approach, this study applies Debbie Lisle's theory of colonial and cosmopolitan visions. This paper analyzes how the main character, who comes from a former colonized country, views herself and the outside world. In the colonial vision, the results show that the main character initially experiences a sense of inferiority towards foreign cultures, while in the cosmopolitan vision, she finds a modern, developed atmosphere through putting forward open-mindedness, harmony, and empathy. In addition, there are several ways the main character conducts in relation to both visions, namely resistance and negotiation. Keywords: colonial vision, cosmopolitan vision, resistance, negotiation